Old Testament pseudepigrapha and the scriptures: [the 61st Colloquium Biblicum Lovaniense took place from July 26 - 28, 2012 in the Maria-Theresia College and the Paus Adrianus VI College of the KU Leuven] - Tigchelaar, Eibert J. C. (Ephemerides theologicae Lovanienses, 2014)
Includes bibliographical references and indexes